MEMOTIVASI PETANI DALAM PENGEMBANGAN PADI ORGANIK DI KECAMATAN SUKOLILO KABUPATEN PATI - Sutrisno Sutrisno (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2018)
ENGLISHThe essence of organic farming is ‘back to the nature’. This paper aims to identify the farmers’ motivation and the management strategy of organic rice in Sukolilo Subdistrict Pati District. This paper concludes: 1) the growth of farmers’ motivation to cultivatethe land with organic farming needs the strengthening. The positive reinforcement might change the behaviour continuously;2) The development of organic farming systems in Sukolilo Subdistrict Pati Regency generally dependson the government's policy framework on agriculture. Therefore, the organic rice development programmust have the vision to strengthen of Indonesian agriculture. Moreover, it should be environment-based as the basic for national independency in the free-market era. The mission should be able to developthe farmer’s bargaining position in the development of agricultural program through a community-based approach, so that the development of the agricultural sector is able to meet the international market demand throughdirected, controlled and sustained program planning. INDONESIAPada hakekatnya pertanian organik adalah back to nature. Tulisan ini bertujuan untuk mengindentifikasi motivasi petani dan strategi pengembangan tanaman padi organik di Kecamatan Sukolilo Kabupaten Pati. Tulisan ini menyimpulkan: 1) Tumbuhnya motivasi petani dalam mengelola lahan dengan sistem pertanian organik perlu diberikan penguatan. Dengan penguatan atau rangsangan yang positif, petani akan mengubah perilaku secara kontinyu atau terus menerus. 2) Kegiatan pengembangan sistem pertanian organik di Kecamatan Sukolilo Kabupaten Pati secara umum tidak terlepas dari kerangka kebijakan pemerintah pada sektor pertanian. Oleh karena itu kegiatan pengembangan padi organik harus memiliki visi membangun kekuatan pertanian Indonesia, berwawasan lingkungan sebagai basis kemandirian bangsa menghadapi era pasar bebas. Misi yang diemban juga hendaknya mampu membangun posisi tawar masyarakat tani dalam pengembangan kegiatan pertanian melalui pendekatan berbasis masyarakat, sehingga pengembangan sektor pertanian mampu memenuhi keinginan pasar internasional, dalam perencanaan program yang terarah, terkendali dan berkelanjutan.